IMPLEMENTASI PENGGUNAAN MODEL PROGRAMER UNTUK MENINGKATKAN AKTIVITAS DAN KETERAMPILAN KERJA SAMA PADA MUATAN IPAS KELAS V SDN WARINGIN KENCANA - Rahayu, Isnaniah; Aslamiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study is the low level of student activity and cooperation in social studies, caused by monotonous and lack of variety in learning, low student engagement, and the limited use of learning models and media, which quickly lead to student boredom. One way to address this issue is by implementing the PROGRAMER model in learning. The purpose of this study was to analyze improvements in student activity, cooperation skills, and learning outcomes. This study used Classroom Action Research (CAR) conducted over four meetings. The subjects were 14 fifth-grade students at SDN Waringin Kencana. This study employed both qualitative and quantitative approaches. Data analysis used descriptive qualitative techniques, described in tables, graphs, and percentage interpretations. The results showed an increase in teacher activity from meetings 1 to 4, with a rating of